(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ethnocultural space of Russia currently poses a problematic area for exploring and finding major solutions heading to protect languages of indigenous minorities of the North, Siberia, and the Far East. The situation with the learning of languages and cultures of small nations is estimated as a recessionary. The purpose of the article is to study the state of ethnocultural education of preschoolers in the North-Eastern regions of the Russian Federation, as well as to determine, on the example of the Republic of Sakha (Yakutia), common problems and ways to improve it. The significance of this study lies in the formulation of the problem of language education of small languages and cultures of the peoples of the North, Siberia, and the Far East in preschool education and finding the ways of preschool education development in modern conditions. The methodological basis of the study was the collection and analysis of statistical data from reports on ethnocultural education of the preschool education departments of Siberia, the Far East and the northern regions of the Republic of Sakha (Yakutia) of the Russian Federation, as well as data from a survey conducted among parents of preschool children.As a result of the study, a comparative analysis of the situation and state of cultural education in preschool institutions of the regions of the Russian Federation was carried out. Common problems have been identified in the field of ethnocultural education of preschoolers in the north-eastern regions of Russia. On the example of the Republic of Sakha (Yakutia), a theoretical justification for the development of ethnocultural and linguistic education is given.